Industry 4.0 in Serbia - state of development - Majstorović, Vidosav; Mitrović, Radivoje; Mišković, Žarko (Serbian Journal of Management, 2022)
A new model of automation of technological systems, based on the Internet, was defined as the concept of Industry 4.0, Germany in 2011. It represents an advanced model of connecting machines and computers (cyber-physical systems - CPS), their networking (cloud computing and Internet of Things (IoT)) with the widespread use of advanced artificial intelligence (AI) in this concept. This concept is a model of smart manufacturing (SM), and today we are talking about: smart vehicles, smart highways, smart grids, smart cities, smart services, etc ... – in short, intelligent "everything and anything" (smart everything). The most important directions for Serbia in the application of Industry 4.0 include: industrial policy for Industry 4.0, education for Industry 4.0 (higher / secondary education), research for Industry 4.0, and especially applied research and readiness of SMEs for Industry 4.0, as well as the application of this model in practice. This paper presents the development and application of the Industry 4.0 model in Serbia, through the activities of the Faculty of Mechanical Engineering in Belgrade, from 2015 until today, with special reference to the application of Industry 4.0 in mining.